Therapeutic strategies for oral lichen planus: State of the art and new insights - Didona, Dario; Caposiena Caro, Raffaele Dante; Sequeira Santos, Antonio Manuel; Solimani, Farzan; Hertl, Michael (Frontiers in Medicine, 2022)
Oral lichen planus (OLP) is a chronic inflammatory disease of oral mucosa. Several clinical subtypes of OLP have been reported, including the reticular and erosive ones. In particular, reticular OLP is usually asymptomatic and is characterized by white streaks surrounded by well-defined erythematous borders. On the other hand, clinical features of erosive OLP are represented by ulcerations and erosions surrounded by erythematous mucosa. While reticular OLP is relatively easy to control, erosive OLP is extremely painful and refractory to therapies, limiting the quality of life of the patients. In addition, treating erosive OLP is extremely tricky and a gold standard treatment has not yet been established. However, several therapeutic approaches have been reported as effective, including systemic corticosteroids, systemic retinoids, and anti-IL-17/anti-IL-23 drugs. In this paper, we reviewed the English- and German-language literature about therapeutic strategies for treating OLP, focusing on new systemic therapies for erosive OLP.